2020
DOI: 10.1038/s41419-020-03037-0
|View full text |Cite
|
Sign up to set email alerts
|

CD44/HA signaling mediates acquired resistance to a PI3Kα inhibitor

Abstract: Most luminal breast carcinomas (BrCas) bearing PIK3CA mutations initially respond to phosphoinositide-3-kinase (PI3K)-α inhibitors, but many eventually become resistant. The underlying mechanisms of this resistance remain obscure. In this work, we showed that a CD44high state due to aberrant isoform splicing was acquired from adaptive resistance to a PI3Kα inhibitor (BLY719) in luminal BrCas. Notably, the expression of CD44 was positively correlated with estrogen receptor (ER) activity in PIK3CA-mutant breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…It is also well documented that Has2 might be a potential therapeutic target via Has2 inhibitor [31]. Moreover, from our recent study, luminallike breast cancer cells preferentially express Has2 or ER with a positive association under pressure of PI3Kα-inhibitory chemotherapy [32]. Taken together, we hypothesize that there might be a potentially novel relationship of ER and Has2 during the development of endocrine therapy resistance.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…It is also well documented that Has2 might be a potential therapeutic target via Has2 inhibitor [31]. Moreover, from our recent study, luminallike breast cancer cells preferentially express Has2 or ER with a positive association under pressure of PI3Kα-inhibitory chemotherapy [32]. Taken together, we hypothesize that there might be a potentially novel relationship of ER and Has2 during the development of endocrine therapy resistance.…”
Section: Introductionsupporting
confidence: 56%
“…Previous studies have indicated that the expression of Has2 was easily in uenced by hormones, including estrogen, and contributed to changes of cell state [25,40]. Moreover, our recent reports identi ed Has2 as a rapid responsive gene upon drug therapy in breast cancer [32]. For the rst time, we demonstrated that Has2 loss was a rapid response to endocrine therapy and played an important role in the acquisition of endocrine resistance.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…This ubiquitous transmembrane molecule is preferentially upregulated in a range of tumors, particularly, in TICs and drug-resistant tumor lesions [ 76 ]. During tumorigenesis, CD44 undergoes extensive alternative splicing generating two isoforms with overlapping and distinct cellular functions: the CD44 variant (CD44v) and CD44 standard (CD44s) isoform [ 77 ]. Although the functional significance of distinct CD44 isoforms in the pathogenesis of cancer is under investigation, the dysregulation of isoform switching has been determined [ 77 ] and implicated in regulating EMT and the adaptive plasticity of cancer cells [ 75 ], potentially generating adaptive therapeutic resistance and tumor recurrence [ 78 ].…”
Section: Cancer Stem Cells In Pancreatic Cancer: Association Of Cell Surface Markers With Tumorigenesis Chemoresistance and Prognosismentioning
confidence: 99%